(untitled) (Tempo e Argumento, 2023)
The Brazilian indigenous peoples, for a long period of time, were narrated from the perspective of the other, situated in a non-place in History. In this historiographical tradition, it is possible to highlight silencing, invisibility, and refusal of a non-Western form of existence. It was only from the end of the 20th century onwards that Amerindian voices began to appear in the Brazilian political, social, educational, and literary scenario. This article discusses writing as an ethical, aesthetic, and political gesture of resistance made by Brazilian Amerindian peoples in the face of current issues and challenges in the educational field. It takes, as an empirical matter, texts by Brazilian indigenous writers. The analysis of this material takes place from the perspective of the History of the Present Time, along with Philosophy, Literature, Anthropology, and Education. It is concluded that writing constitutes a major ethical, aesthetic, and political device of struggle and resistance for these peoples, however, without denying their oral tradition.